PATTERN ADAPTION OF STUDENTS WHO PERFORCE ENTERING ISLAMIC BOARDING SCHOOL - Lailil Mukarromah; Suryanto Suryanto; Amanda Amanda (SCHEMA (Journal of Psychological Research), 2018)
The purpose of this research was to know how the adaption pattern or self adaption of students who perforce entering islamic boarding school because of their parents’ choice in Al Amanah Modern Islamic boarding school. Besides, this research was also purposed to know what factors which hampered and supported the adaption process in that school. The research used qualitative methode with case-study approach. The informen were three 7th grade-girl students who perforce entering the boarding school by their parents in Al Amanah Modern Islamic boarding school. Data collecting used Deeply Interview methode. According to the research result, showed that students who perforce entering boarding school needed more time to adapt and should have ability or skill to handle stressor to increase their achievement. Many rules in boarding school made them get difficulty to adapt. Meanwhile, by making more friends who had same problem and motivating each other can support the adaption process.